2000
DOI: 10.1359/jbmr.2000.15.4.721
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Prior Fractures Have an Increased Risk of Future Fractures: A Summary of the Literature and Statistical Synthesis

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

39
815
3
67

Year Published

2002
2002
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,767 publications
(924 citation statements)
references
References 52 publications
39
815
3
67
Order By: Relevance
“…It might be related to differences in the study populations, especially with regard to age and the type of incident fractures (hip versus other fractures) or the methods used. As already reported, (18)(19)(20) and not surprisingly, our study confirms that a history of a fragility fracture is a powerful predictor of future fracture independent of BMD. The multivariable-and BMD-adjusted risk of a major OP fracture was 2.3-to 2.5-fold higher in women who had reported a prior low-trauma fracture after the age of 45 years compared with women without a prior fracture history.…”
Section: Discussionsupporting
confidence: 91%
“…It might be related to differences in the study populations, especially with regard to age and the type of incident fractures (hip versus other fractures) or the methods used. As already reported, (18)(19)(20) and not surprisingly, our study confirms that a history of a fragility fracture is a powerful predictor of future fracture independent of BMD. The multivariable-and BMD-adjusted risk of a major OP fracture was 2.3-to 2.5-fold higher in women who had reported a prior low-trauma fracture after the age of 45 years compared with women without a prior fracture history.…”
Section: Discussionsupporting
confidence: 91%
“…M any studies have shown increased fracture risk (1)(2)(3) and mortality (4)(5)(6)(7)(8) after clinical vertebral fracture. Even subjects with no clinical fracture and little pain but with vertebral deformity detected by X-ray showed slightly increased mortality.…”
Section: Introductionmentioning
confidence: 98%
“…In one systematic review, the risk factor for having a new vertebral fracture in women that have already fractured one vertebra was 4.4 times higher than those without fracture [1]. Moreover, prior vertebral fracture was also a good predictor for hip, forearm and any other non-vertebral fractures.…”
Section: Introductionmentioning
confidence: 99%